5x-(4+8x)=20

Simple and best practice solution for 5x-(4+8x)=20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(4+8x)=20 equation:


Simplifying
5x + -1(4 + 8x) = 20
5x + (4 * -1 + 8x * -1) = 20
5x + (-4 + -8x) = 20

Reorder the terms:
-4 + 5x + -8x = 20

Combine like terms: 5x + -8x = -3x
-4 + -3x = 20

Solving
-4 + -3x = 20

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + -3x = 20 + 4

Combine like terms: -4 + 4 = 0
0 + -3x = 20 + 4
-3x = 20 + 4

Combine like terms: 20 + 4 = 24
-3x = 24

Divide each side by '-3'.
x = -8

Simplifying
x = -8

 

See similar equations:

| 9=-4 | | 0.2+0.6(0.4-0.3)*2= | | -11=x+10 | | 5x+9-3=54 | | x^2-6x-72=0 | | 10-15x+(2x-5)=x-30 | | x-x=4y | | 34x+11x-6=62 | | 3y-1=1+3y | | 9-k=32 | | -3x+-5=-20 | | 2x(x-3)-13=0 | | (x+2)(x-4)=2x(x-3)-13 | | x^2-4x-16=0 | | -(-2x-4)+(8x-7)=1-(-12x+9) | | 3x=10+x | | 4x-4=0 | | 14-(-46)=x | | 8+2z-7=8z+17-2z | | z^3+125=0 | | -14-3x=-9 | | 8k-7=-11+7k | | 4(b+4)=0 | | -12x-4=32-8x | | 0.2x^2+0.6x^2-0.3x^2= | | -(5y+1)-(-4y-6)=1 | | 12x-19=3x+8 | | 7m-12=2.5m+12 | | 150-5x=x | | x+3.45=7.04 | | 5-x=45 | | 8(p-4)=2(2p+1) | | 0.2x-1.4=15.82-0.5x | | 3(6-x)+2x=15 | | 2x^2-9x+8=0 | | 2a(a-5)=4(a-5) | | 5+(6x+4)+(3x-1)-8x=(2-7x)-25 | | 2+2[4-6*3(4+6*2)*3-6]-14= | | 0=-t^2+4t+5 | | e+3/4=1 | | 6x-3=-15+2 | | 6x+84=12x-12 | | -16=21+h | | xy^3*xy^2= | | p=460 | | 0.05(0.3n+35n)-0.8(-0.09n-22m)= | | 5x^2-32=0 | | 4x-2=16-2x | | 5y^3-9y^2-2y=0 | | 5x^2-36=0 | | x^2-10x+61=0 | | y=x^2+11x+28 | | 13-9x=218-44x | | 52-3x=6x+15 | | 2a*2a+3=7a | | 36-[4+4y-2(y+4)]=-4(4y-6)-[9(y-1)-20y+17] | | -16t^2+85t+10=20 | | a^2+9a+18=0 | | 12y-5=60-y | | x^4-27x^2+176=0 | | 9x=9x+5 | | 2x+5=5(x+1)-3x | | 7X=2X+-15 | | 3x-(9x+4)=12-6x | | 4(x-4)=6x-4-2x |